PENGARUH PRENATAL YOGA TERHADAP KECEMASAN IBU HAMIL DALAM MENGHADAPI PERSALINAN DI TPMB LINA ROSIANA JAKARTA TIMUR - Ayu Syafa Atunisa; Suprihatin; Jenny Anna Siauta (KHD Production, 2024)
Anxiety is one form of psychological change in pregnant women. Pregnant women are vulnerable to mental health problems because of the changes they experience at various stages which affect their mental health. The anxiety level of pregnant women can be reduced with non-pharmacological measures, namely prenatal yoga. This study aims to determine the effect of prenatal yoga on the anxiety of third trimester primigravida pregnant women facing labor at TPMB Lina Rosiana, East Jakarta. This research method uses a quasi-experiment with a pre-test and post-test with a control group design. The sample in this study consisted of 34 third trimester primigravida pregnant women who were divided into 2 groups, namely 17 control groups and 17 experimental groups. Samples were taken using purposive sampling. The pain assessment instrument used is the anxiety skinning questionnaire, namely PASS, which has been proven valid and reliable. Data were analyzed using the Paired t-test to determine differences in anxiety within one group and the independent t-test to determine differences in anxiety between groups. The results of the study showed that there was a difference in the level of anxiety in the experimental group before and after being given prenatal yoga, with a P-value of 0.000 and there was a difference in the level of anxiety between the experimental group and the control group with a p-value of 0.000.